Evaluasi penerapan konsep forest city dalam pembangunan berkelanjutan lokasi calon ibu kota negara Indonesia - Nurfatiha, Alin E.; Nugraheni, Dessy Tri; Febriana, Ratu L. N.; Miftadira, Rendra (Institute for Advanced Science Social, and Sustainable Future, 2024)
Jakarta being the nation’s capital, has led to significant environmental stress due to population density. The rise in inhabitants corresponds with the demand for residential land, urban infrastructure, and other auxiliary structures. The Indonesian government proposes the relocation of the State Capital as a remedy to address the issues and loads present in Jakarta and, more extensively, on Java Island. The fair allocation of funds for infrastructure development to boost economic growth outside Java Island is targeted at suitable locations, specifically in the North Penajam Paser and Kutai Kartanegara Regencies. The forest city concept is a strategy in urban planning and development that integrates with nature to safeguard forest regions and biodiversity. Striving for sustainable development necessitates consideration of social, economic, and environmental aspects in the urbanization process on Kalimantan Island. Urbanization issues to general environmental paradigms often arise in several regions, offering a unique viewpoint on the implementation of urban forests at the State Capital candidate location. The shift of service and government hubs is accompanied by population redistribution, with an estimated 1.5 million individuals expected to inhabit the proposed area. Social and environmental conflicts are prevalent issues of concern in the establishment of new cities. The objective of the evaluation is conducted through an analysis of the potential and challenges that will be encountered in relocating the State Capital from the socio-cultural aspect concerning cultural assimilation and environmental aspects related to the urban environment, which can induce an urban heat island. This research employs a descriptive qualitative approach and method to identify potential and problems developed by the necessary strategies through SWOT analysis. The findings of this research offer recommendations that the government, as the decision-maker, must implement to preserve and sustain the potential of the environment and socio-cultural diversity.